Multi-functional BST2/tetherin against HIV-1, other viruses and LINE-1 - Zhao, Yifei; Zhao, Ke; Wang, Shaohua; Du, Juan (Frontiers in Cellular and Infection Microbiology, 2022)
Bone marrow stromal cell antigen 2 (BST2), also known as CD317, HM1.24, or tetherin, is a type II transmembrane glycoprotein. Its expression is induced by IFN-I, and it initiates host immune responses by directly trapping enveloped HIV-1 particles onto the cell surface. This antagonistic mechanism toward the virus is attributable to the unique structure of BST2. In addition to its antiviral activity, BST2 restricts retrotransposon LINE-1 through a distinct mechanism. As counteractive measures, different viruses use a variety of proteins to neutralize the function or even stability of BST2. Interestingly, BST2 seems to have both a positive and a negative influence on immunomodulation and virus propagation. Here, we review the relationship between the structural and functional bases of BST2 in anti-HIV-1 and suppressing retrotransposon LINE-1 activation and focus on its dual features in immunomodulation and regulating virus propagation.